Optimization of headspace temperature and time sampling for identification of palm sugar volatile components using response surface methodology - Ho , Chun Wai; Wan Aida Wan Mustapha,; Mohd. Yusof Maskat,; Osman Hassan, (Universiti Kebangsaan Malaysia, 2005)
The aim of this work was to optimize equilibration temperature and time for analyzing volatiles components in palm sugar (Arenga pinnata) by headspace solid phase micro-extraction (HS-SPME) method. A 50/30 lm DVB/CAR/PDMS fiber was used to adsorb the volatile components from the headspace region. A central composite statistical design was used to evaluate the effects of different temperatures (40 to 60°C) and sampling time (5 to 25 min) on the total yield of palm sugar volatile components. Response surfaces were plotted, and these together with results from some additional experiments (axial and center points) produced optimal extraction conditions for HS-SPME at 55°C and 12 min. These conditions were similar to N-heterocyclic compounds where the relative percentage area (RPA) was > 88.0% of total volatiles.